Topics on discrete mathematics and combinatorics - ȚURCAȘ, George Cătălin; BAGDASAR, Ovidiu; ANDRICA, Dorin (Presa Universitară Clujeană, 2025)
The book presents modern results in discrete mathematics and combinatorics, its purpose being to popularise recent developments in this area, and to encourage further research. Structured in ten chapters, it provides theoretical results illustrated by many examples and applications.